Juridical Analysis of the Fulfillment of the Rights of Children of Rape Perpetrators from the Perspective of National Law and Qanun Jinayat - Rizqi Hidayat Mizan; Rizanizarli Rizanizarli; Sulaiman Sulaiman (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
This study analyzes the legal protection of children as perpetrators of rape within Indonesia’s national legal system and Aceh’s Qanun Jinayat, focusing on the Syar’iyah Court’s decisions that often fail to confirm the fulfillment of children’s rights to education, rehabilitation, and reintegration. Although the principle of the best interests of the child requires comprehensive protection, the absence of clear implementing regulations has created uncertainty. Using a normative juridical method with legislative and case approaches, the research draws on secondary data enriched with primary data and qualitatively analyzed. The findings show that both national law and Qanun Jinayat emphasize child protection based on the best interests principle. National law mandates special procedures such as mentoring, closed hearings, psychological assessments, and diversion, while Qanun Jinayat, through Article 50, stipulates lighter and proportionate uqubat for children. These frameworks complement each other in ensuring education, psychological recovery, and social reintegration. However, several Syar’iyah Court decisions have not explicitly included recovery rights, resulting in ineffective protection and legal uncertainty. The study recommends that the Syar’iyah Court explicitly incorporate children’s rights to education, rehabilitation, and reintegration in its verdicts. Furthermore, the Aceh Government should issue Standard Operating Procedures or Governor’s Regulations to provide a clear legal basis for implementing child uqubat in line with the Juvenile Criminal Justice System.